Experience and management of COVID 19 in Lima Norte - Ramírez Atencio, Claudio (2021)
This paper shows the experience lived in the Dirección de Redes Integradas de Lima Norte (DIRIS Lima Norte) in the face of the COVID-19 pandemic, where it was tackled ingeniously and boldly, with scarce resources and alternative solutions, to every difficulty encountered in full uncertainty, due to how little was known about the disease. From the success of the work against coronavirus at DIRIS Lima Norte, models emerged that became public policies in Peru. This contribution shows some alternative solutions, linked to the MINSA, that have contributed to reduce the impact of coronavirus by strengthening governance, promoting and disseminating measures of self-care and personal protection against SARS-Cov2, in addition to the preparations that today allow the prompt vaccination of the population with risk factors in the jurisdiction of North Lima.